The application of knowledge stylised facts in West Africa Economic and Monetary Union (WAEMU) - Nogbou Andetchi Aubin Amanzou; Zie Ballo; Sery Guy Flavien Troupa (Journal of Innovation and Entrepreneurship, 2022)
Sub-Saharan Africa has one of the dynamic economies in the world. Unfortunately, the performance achieve has not led to a reduction of social issues. So, the government are making massive investment to overcome social issues. This massive public investment highlights the exogenous nature of the current economic growth. So, a change of the strategy in the economic management of sub-Saharan Africa is required. One solution remains the change of economic paradigm: the transition from exogenous economic with decreased return to endogenous economic with increased return. The theoretical explanation of such arguments are supported by New Growth Theory. However, the implementation of the new theory required compliance to a set of indicators known as stylized facts. In 2009, Romer and Jones have developed a list of stylized corresponding to the need of New Growth Theory. The stylized facts of the West African Economic and Monetary Union (WAEMU) have been compared to the standard facts of Romer and Jones in order to apply the recommendations of New Growth Theory in this area. To reach that aim, the stylized facts have been described and analysed with econometric panel model. As result, we find that the description of the stylized facts in WAEMU fitted perfectly with that of Romer and Jones for the same period. Unfortunately, when using data, institution don't work as expected by Romer and Jones. This study strengthens the argument for the implementation of economic policy based on the valorisation of knowledge economic in WAEMU.
Keywords: D83; N17; O11; O17; O40; 650; Africa; Economic development; Economic growth; Knowledge economic; Macroeconomic Analyses